Progressive Neurological Deficit in Adult Idiopathic Syringomyelia (IS): Case Report and Literature Review - Yudoyono, Farid; Widhiatmo, Anugrah O.; Wirjomartani, Beny A. (Journal of Medicine and Health, 2016)
A syringomyelia is a clinical entity of any tubular fluid-filled cavity within the spinalcord that causes slowly but relentlessly progressive symptoms as well as expansion of thecavity, which is most commonly associated with Chiari malformation Type I, which due toadvancement of imaging techniques has resulted in more incidental idiopathic syringes that arenot associated with tumor, trauma, or postinfectious causes. Idiopathic syringomyelia (IS) is apathological entity in which no overt etiology is evident for a syrinx. In this study, we describe acase in a 45 year-old woman presented with progressive difficulties in walking and also hadmyelopathic signs evidenced by hyperreflexia in the lower extremities and underwent foramenmagnum decompression and C1 lamiectomy. Idiopathic syringomyelia is a pathological entityin which no overt etiology is evident for a syrinx. It can be managed succesfully byconservative treatment but if there is a progression of neurological deficit, surgicaldecompression is a mandatory.Keywords: idiopathic syringomyelia, neurological deficit